Pengaruh integrasi intervensi gizi dan stimulasi tumbuh kembang terhadap peningkatan berat badan dan perkembangan balita kurus - Bunga Astria Paramashanti; Sulistyawati Sulistyawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Indonesia has faced the problem where double burden malnutrition increasing. On the other hand, malnutrition in children may affect the development both in early childhood and the quality of human capital in later life.Objective: This study aimed to examine the effect of integration of nutrition intervention and development stimulation on weight gain and development of wasted children.Method: Design used in this study was quasi-experimental with pre- and post-test control group. Subjects were 38 children under-five resided in Sedayu Subdistrict. Sampels were selected by using total sampling of children under-five in community feeding center, meanwhile controls were children under-five selected from integrated health posts in another villages with the ratio of 1:1. Interventions given were education, development stimulation and food supplementation package distributed by the community health workers whom were given capacity building. Analysis used were Mann-Whitney U and Wilcoxon Signed Rank tests at the level of significance 0,05.Results: Children in intervention groups gained their weight significantly from before (9.17±1.89) and after (9.27±1.79) intervention (p=0.04). Meanwhile, development impairment score decreased from 1.32±0.75 to 0.42±0.61 significantly (p=0.00).Conclusion: Intervention package containing nutrition and development education, development stimulation and supplementary food through community feeding center (CFC) sucessfully increased body weight and development of wasted children significantly.